Misregulation of the IgH Locus in Thymocytes - Kumari, Gita; Gerasimova, Tatiana; Du, Hansen; De, Supriyo; Wood, William H.; Becker, Kevin G.; Sen, Ranjan (Frontiers in Immunology, 2018)
Functional antigen receptor genes are assembled by somatic rearrangements that are largely lymphocyte lineage specific. The immunoglobulin heavy chain (IgH) gene locus is unique amongst the seven antigen receptor loci in undergoing partial gene rearrangements in the wrong lineage. Here we demonstrate that breakdown of lineage-specificity is associated with inappropriate activation of the Eµ enhancer during T cell development by a different constellation of transcription factors than those used in developing B cells. This is reflected in reduced enhancer-induced epigenetic changes, eRNAs, formation of the RAG1/2-rich recombination center, attenuated chromatin looping and markedly different utilization of DH gene segments in CD4+CD8+ (DP) thymocytes. Additionally, CTCF-dependent VH locus compaction is disrupted in DP cells despite comparable transcription factor binding in both lineages. These observations identify multiple mechanisms that contribute to lineage-specific antigen receptor gene assembly.